DETECTION OF ENTEROTOXIN GENES OF STAPHYLOCOCCUS AUREUS ISOLATES FROM RAW MILK . - Mohammed H. Khudor (Basrah Journal of Veterinary Research)
A total of 200 samples of raw milk (100 cow milk and 100 buffaloe milk) were collected from different markets in Basrah city and were analyzed for the presence of Staphylococcus aureus . Results indicate that this bacterium was observed in 28.5% of total samples (30% of cow milk and 27% of buffalo milk) Enterotoxin genes (Sea-See) were investigated using a polymerase chain reaction (PCR). Staphylococcal enterotoxin C gene ( Sec ) was detected in 24.56% of the S. aureus isolates , while none of the S. aureus isolates harbouring Sea, Seb,Sed or See genes.